Genotypic Variation and Genotype-by-Environment Interactions in Growth and Wood Properties in a Cloned Eucalyptus urophylla × E. tereticornis Family in Southern China. Issue 3 (7th March 2018) - Yang, Heyu; Weng, Qijie; Li, Fagen; Zhou, Changpin; Li, Mei; Chen, Shengkan; Ji, Hongxia; Gan, Siming
Abstract: Using a cloned Eucalyptus urophylla × E. tereticornis family, the present study estimated clonal mean repeatability, inter-trait correlation, and clone-by-site interactions for height ( H ) and diameter at breast height ( D ) across 0.5–8 years of age as well as 8-year-old wood basic density ( BD 8 ), cellulose content ( CC 8 ), hemi-cellulose content ( HC 8 ), Klason lignin content ( LC 8 ), and lignin syringyl-to-guaiacyl ratio ( S/G 8 ). Clonal mean repeatability estimates were 0.40–0.91 for growth traits H and D over 0.5–8 years and 0.50–0.87 for wood properties at age 8 for three separate sites (except that of 0.01 for HC 8 at Yanxi) and across sites, indicating moderate to high levels of genetic control of the traits investigated. H had high positive genetic correlation with D . Growth traits ( H and/or D ) showed generally positive genetic correlation with BD 8 and CC 8 while negative with HC 8 and LC 8 . Significant genotype-by-environment (clone-by-site) interactions were observed for most traits, suggesting that clones should be matched to sites to increase genetic gain. Our results suggest that there is potential to use E. urophylla × E. tereticornis clones to increase yield with desirable wood properties in Southern China.